Structural Changes Due to Antagonist Binding in Ligand Binding Pocket of Androgen Receptor Elucidated Through Molecular Dynamics Simulations - Sakkiah, Sugunadevi; Kusko, Rebecca; Pan, Bohu; Guo, Wenjing; Ge, Weigong; Tong, Weida; Hong, Huixiao (Frontiers in Pharmacology, 2018)
When a small molecule binds to the androgen receptor (AR), a conformational change can occur which impacts subsequent binding of co-regulator proteins and DNA. In order to accurately study this mechanism, the scientific community needs a crystal structure of the WT-AR ligand binding domain bound with antagonist. To address this yet to be open need, we leveraged molecular docking and molecular dynamics simulations to construct a structure of the WT-AR ligand binding domain bound with antagonist bicalutamide. The structure of mutant AR (Mut-AR) bound with this same antagonist informed this study. After molecular docking analysis pinpointed the suitable binding orientation of a ligand in AR, the model was further optimized through 1 microsecond of molecular dynamics simulations. Using this approach, three molecular systems were studied: 1) WT-AR bound with agonist R1881, 2) WT-AR bound with antagonist bicalutamide, and 3) Mut-AR bound with bicalutamide. Our structures were very similar to experimentally determined structures for both WT-AR with R1881 and Mut-AR with bicalutamide, demonstrating the trustworthiness of this approach. In our model, when WT-AR is bound with bicalutamide, Val716/Lys720/Gln733, or Met734/Gln738/Glu897 move and thus disturb the positive and negative charge clumps of the AF2 site. This disruption of the AF2 site is key for understanding the impact of antagonist binding on subsequent co-regulator binding. In conclusion, the antagonist induced structural changes in WT-AR detailed in this study will enable further AR research and will facilitate AR targeting drug discovery.